Serum apolipoprotein A-I potentiates the therapeutic efficacy of lysocin E against Staphylococcus aureus - Hiroshi Hamamoto (Nature Portfolio, 2021)
Lysocin E is a lipopeptide with antibiotic activity against methicillin-resistant Staphylococcus aureus. Here, the authors show that the antimicrobial activity of lysocin E is potentiated through interactions with host serum proteins (such as apolipoprotein A-I) and bacterial membrane components.